2008
DOI: 10.1007/s11242-008-9254-4
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model of Coalbed Gas Flow with Klinkenberg Effects in Multi-Physical Fields and its Analytic Solution

Abstract: The deep-mining coal seam impacted by high in situ stress, where Klinkenberg effects for gas flow were very obvious due to low gas permeability, could be regarded as a porous and tight gas-bearing media. Moreover, the Klinkenberg effects had a significant effect on gas flow behavior of deep-mining coal seam. Based on the gas flow properties of deep-mining coal seams affected by in situ stress field, geothermal temperature field and geoelectric field, a new mathematical model of coalbed gas flow, which reflecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 10 publications
(10 reference statements)
0
19
0
Order By: Relevance
“…In traditional coal mining, CBM is considered a type of hazardous gas, not only because of the danger of explosions and gas outbursts, but also because of serious threat to the safety of mine production [1][2][3][4][5][6]. In contrast, CH4, the main ingredient of CBM, is a greenhouse gas, whose greenhouse effect is ~21-23 times as strong as that of CO2 [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In traditional coal mining, CBM is considered a type of hazardous gas, not only because of the danger of explosions and gas outbursts, but also because of serious threat to the safety of mine production [1][2][3][4][5][6]. In contrast, CH4, the main ingredient of CBM, is a greenhouse gas, whose greenhouse effect is ~21-23 times as strong as that of CO2 [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the coal seams in America and Australia are of little depth and high permeability, and surface well predrainage and underground directional long borehole drainage technologies are their major and minor strategies, respectively. Part of Germany and Poland are similar to the coal seam conditions in Chinese mining areas; however, their yields are low and the number of underground coal seams is relatively small; and the gas drainage is mainly dependent on the underground cross-measure boreholes gas drainage technology [1][2][3][4][5][6]15]. In contrast, the Chinese coal seams are of larger depth and high ground stress; therefore, underground drainage is the main approach to extract CBM.…”
Section: Introductionmentioning
confidence: 99%
“…The coal and gas outbursts have become the major natural disasters that challenge coal mine safety (Yuan, 2016). According to statistics, the secondary disasters caused by coal and gas outbursts account for more than 80% of the major coal mine accidents that have occurred (Hu et al, 2009a(Hu et al, , 2009b. Therefore, China has been one of the countries suffering from a serious coal and gas outburst problem (Hu et al, 2009a(Hu et al, , 2009b(Hu et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…According to statistics, the secondary disasters caused by coal and gas outbursts account for more than 80% of the major coal mine accidents that have occurred (Hu et al, 2009a(Hu et al, , 2009b. Therefore, China has been one of the countries suffering from a serious coal and gas outburst problem (Hu et al, 2009a(Hu et al, , 2009b(Hu et al, , 2015. Studies have shown that the actual outbursts area accounted for only 10 to 20% of the total areas of coal seam (He and Chen, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, "desorption" means a number of processes resulting in the release of the sorbing gas from the sorbent. When speaking about the release of methane from a coal bed into an excavation, we typically mean the combination of the filtration (Crank 1975;Timofejew 1967;Pillalamarry et al 2011;Hu et al 2009;Wu et al 1998), diffusion, and sorption processes, which will further be referred to as "the sorption proper" (Harpalani and Chen 1997;Pillalamarry et al 2011;Day and Sakurovs 2008;Weniger et al 2010;CeglarskaStefańska and Zarębska 2005;Majewska et al 2009;Busch and Gensterblum 2011;Nagaoka and Imae 2003). Under laboratory conditions, in which case the investigations are carried out for small-sized grain samples, we can assume that the transportation of gas is influenced mainly by the diffusion processes.…”
Section: Introductionmentioning
confidence: 99%